Penguatan Paradigma Profesi Guru AbAd 21 : Konsep guru Abad 21 dan Tantangan dan keterampilan guru di abad 21 - Herawati, Fitri Indriani; Aminarti, Dini; Rosdiana (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
strengthening the teaching profession in Indonesia in various aspects of teaching career development, aspects of teaching development and aspects of professional development. Professionalism in teachers is important in the 21st century because it is required to be able to change the educational curriculum in accordance with the curriculum in the 21st century. In the success of facing education in the 21st century, teachers must be professional and responsible for the educational process. The challenges of the 21st century are (1) life and work skills, (2) learning and innovation skills, (3) media and technology skills (partnership) for 21st century skills, these three skills are summarized in a scheme referred to as the 21st century knowledge skills rainbow.